Mechanical Behavior of Ion-Exchanged Alkali Aluminosilicate Glass Ceramics - Bruno M. F. Nunes; André Dinis; Jorge C. Fernandes; Rui M. Almeida; Luís F. Santos (Crystals)
Glass is one of the oldest and most versatile manmade materials and has been used for centuries. One of the areas of significant research and progress is that of high-mechanical-resistance glass. Several processes can be used to maximize the mechanical strength of glasses, namely thermal or chemical treatments. Glass ceramics, obtained through controlled crystallization, can enhance the mechanical properties of these materials and, as long as the crystals remain small enough, transparent glass ceramics can be obtained. On the other hand, ion exchange can strengthen the glass surface and reduce failure. As a result, ceramization followed by ion exchange can further enhance the mechanical characteristics of the parent glass. Aluminosilicate glasses and glass ceramics are known to present excellent transparency and chemical durability, plus good mechanical behavior; therefore, a lithium aluminosilicate glass composition was studied in order to obtain transparent glass ceramics, followed by an ion exchange process, and its mechanical properties were studied. Transparent glass ceramics were obtained, with an increase of ~15% in hardness over the parent glass. The glass ceramics were then subjected to an ion exchange treatment in a KNO3 bath, in order to further enhance the mechanical properties, without hindering the optical transmittance. The combination of heat treatment and chemical treatment resulted in a cumulative hardness increase of ~25%, from 620 ± 10 HV, for the as-cast glass and from 773 ± 23 HV for the ion-exchanged glass ceramic. Regarding the indentation fracture toughness, values obtained for the glass ceramics were similar to those obtained for the cast glass, yielding no noticeable change. Indentation fracture toughness increased after the ion exchange treatment of the glass ceramic, since a much higher load was necessary to obtain a measurable indentation, indicating higher indentation fracture strength.